Financial performance trends of United States Hockey Inc: a resource-dependency approach - Omondi Ochieng, Peter (2019)
Purpose. The purpose of this paper is to examine the 2009 to 2016 financial performance of the US Hockey Inc., using financial effectiveness indicators and financial efficiency ratios. Design/methodology/approach. With the assistance of financial trend analysis, archival data were used to examine the financial performance (evaluated by net income), financial effectiveness (indicated by total assets and total revenues) and financial efficiency (examined by programme services ratios and return on assets) of US Hockey Inc. Findings. On average, the financial performance of the organization was positive ($30,895 net income per year). Financial effectiveness was steady with increases in assets and revenues. Financial efficiency was poor with 79% of revenues spent on programme services and 1.45% average return on asset. Research limitations/implications. The results can be generalized to similar national non-profit sports federations but not corporate sports entities with dissimilar financial goals. Practical implications. The results revealed that national non-profit sports federations can boost their financial performance by maintaining a double strategically focus on both financial effectiveness and financial efficiency. Originality/value. The study used both financial effectiveness and financial efficiency measures to evaluate the financial performances of a national non-profit sports federation – a neglected approach similar studies. Doi: https://doi.org/10.1108/JEFAS-02-2018-0022